The effects of Covid-19 toward public relations practitioner in Malaysia / Abd Rauf Ridzuan ... [et al.] - Ridzuan, Abd Rauf; Ramzi, Miza Izzati; Rashid, Aqilah; Ismail, Norzuraini; Mohamed Nasir, Hidayah; Kad Rusman, Kamilia; Zaulkiflee, Jihan (Faculty of Communication & Media Studies, 2021)
In this globalization, all country in the world are facing the COVID-19 pandemic. It's getting harder when the government arrange the Movement Control Order (MCO) towards country. There were many who have lost their jobs and struggled to cope with the new normal during the COVID-19 pandemic. Public relations practitioner in government and private sector are among those who are having a difficult time which they have to contribute to the department and companies. The objective of this research is to ask about how public relations practitioner handles their work during pandemic COVID-19, to investigate the challenges that public relations practitioner face during the COVID-19 pandemic and to identify about public relations practitioner opinion on the roles of public relations during pandemic COVID-19. The researchers will research on the effects of COVID-19 toward public relations practitioner during the COVID-19 pandemic through the use of qualitative research, an interview will be conduct to gathers all information about the topic. The total of the companies that is a part of this research is Bank Rakyat, Jabatan Pertanian Pulau Pinang, Parliamentary Corporate, Afiq Rashid Public Relations and Media Prima which there is few from government sector and some from private sector. The findings of this research proves that public relations practitioners facing a hard times and crisis during this pandemic.